2014
DOI: 10.4049/jimmunol.1400918
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase in Neutrophils and Endothelium Contributes to Ischemic Brain Injury in Mice

Abstract: Nitric oxide produced by inducible nitric oxide synthase (iNOS) contributes to ischemic brain injury, but the cell types expressing iNOS and mediating tissue damage have not been elucidated. To examine the relative contribution of iNOS in resident brain cells and peripheral leukocytes infiltrating the ischemic brain, we used bone marrow (BM) chimeric mice in which the middle cerebral artery was occluded and infarct volume was determined 3 days later. iNOS−/− mice engrafted with iNOS+/+ BM exhibited larger infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 57 publications
(67 reference statements)
7
75
0
Order By: Relevance
“…For instance, iNOS -knockout mice were resistant to behavioral and synaptic deficits or cerebral plaque formation and premature mortality in animal models of AD (Medeiros et al, 2007; Nathan et al, 2005). These iNOS -knockout mice were also protected from dopaminergic neurodegeneration in mouse models of PD (Kumar et al, 2015; Liberatore et al, 1999) and ischemic brain injury (Garcia-Bonilla et al, 2014), as similar to their resistance to inflammatory diseases and peripheral tissue injury caused by alcohol and non-alcoholic substances (Nobunaga et al, 2014; Spruss et al, 2011). In addition, nNOS seems to be responsible for DNA damage in a mouse model of PD (Hoang et al, 2009).…”
Section: Consequences Of Increased Nitroxidative Stressmentioning
confidence: 76%
See 1 more Smart Citation
“…For instance, iNOS -knockout mice were resistant to behavioral and synaptic deficits or cerebral plaque formation and premature mortality in animal models of AD (Medeiros et al, 2007; Nathan et al, 2005). These iNOS -knockout mice were also protected from dopaminergic neurodegeneration in mouse models of PD (Kumar et al, 2015; Liberatore et al, 1999) and ischemic brain injury (Garcia-Bonilla et al, 2014), as similar to their resistance to inflammatory diseases and peripheral tissue injury caused by alcohol and non-alcoholic substances (Nobunaga et al, 2014; Spruss et al, 2011). In addition, nNOS seems to be responsible for DNA damage in a mouse model of PD (Hoang et al, 2009).…”
Section: Consequences Of Increased Nitroxidative Stressmentioning
confidence: 76%
“…However, NO, produced at greater amounts (0.1 – 1 µM) usually by iNOS and nNOS or in inflammatory disease states, can act as a neurotoxic agent and is believed to nitrate many proteins in the neuron, causing cell death and severe tissue injury (Brown, 2010; Dai et al, 2013; Franco et al, 2013). For instance, large amounts of NO seems to be important in causing ischemic brain injury (Garcia-Bonilla et al, 2014) and many other neuronal diseases (Butterfield et al, 2007, 2014). Direct evidence for the involvement of iNOS in neuronal diseases was provided by the experimental results of using iNOS -knockout mice, a specific inhibitor of iNOS 1400W (Kumar et al, 2014), or an anti-sense oligonucleotide specific to iNOS (Maggio et al, 2012).…”
Section: Consequences Of Increased Nitroxidative Stressmentioning
confidence: 99%
“…Accumulating evidence suggests this intracerebral neutrophil infiltration has potentially damaging pro-inflammatory consequences in cerebral ischemia and highlights a crucial role of neutrophils in the prevention and treatment of stroke [5,7,9,10]. A recent study also showed that neutrophils and neutrophil-derived iNOS contribute to ischemic brain injury [26]. In accordance with those findings, our results showed that permanent cerebral ischemia increased the number of circulating neutrophils, chemotaxis, and endothelium adhesion, up-regulated neutrophil iNOS/NO expression, and promoted neutrophil intracerebral infiltration.…”
Section: Discussionmentioning
confidence: 94%
“…After initial adherence, neutrophils will follow a chemokine and activator gradient produced by the injured tissue. Neutrophils reach peak numbers at 2~4 days after ischemic stroke and then decrease thereafter [6364]. During this period, pro-inflammatory neutrophil activation contributes to disruption of blood brain barrier, increased infarct size, hemorrhagic transformation, and worse neurologic outcomes.…”
Section: Infiltrated Leukocytes Exacerbate Ischemic Strokementioning
confidence: 99%